Research Progress and Governance Prospect of Marine Biodiversity Conservation Synergistic Response to Climate Change - LIN Ruijuan; JIANG Yuhuan; CHEN Fenggui; TAN Hongjian; ZHANG Jiwei (Haiyang Kaifa yu guanli)
Climate change and loss of marine biodiversity are the two interrelated global crises. The paths, methods and policies of the synergies between them have attracted the increasing attention of the international community and have become a hot topic of current scientific research. This study aims at promoting a systematic understanding of the international research progress and frontier trends in this field. Firstly, this paper starts from the key concepts and policy orientation of marine biodiversity protection in response to climate change, and further summarizes the overall research progress, content framework and development trend in this field. On this basis, the conceptual framework of synergistic governance of marine biodiversity protection and climate change response is put forward from the dimensions of factors (such as objectives, processes, objects and subjects) and structure. Furthermore, this paper focuses on the synergy of four basic elements: multi-domain objectives, cross-system processes, cross-regional integration and multi-stakeholder co-governance, and looks forward to the practical pathway to promote the development and improvement of the synergistic governance system and capacity for marine biodiversity protection in response to climate change in the future.